INCIDENCE PATTERN OF SOME INSECT PESTS OF SESAMUM IN WEST BENGAL. - PAUL, SAMBIIU KUMAR KUMAR; JIIA, SHANTANU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
The field study was conducted for two consecutive seasons during 2003 & 2004 at Kalyani , Nadia, West Bengal. The incidence pattern of three insect pests WI . Cryptopeltis tenuis L. (Miridae :Hem i ptera) , Dolycuris indices Stant.(Pentatom idae : Hemiptera) and Pachnephorus histreutes Muls . (Chrysomelidae : Coleoptera) on sesame (Sesannen indictee L.) at different dates of sowing revealed that the three pests appeared on the crop in between last week of March to early week of April in both the seasons. The duration of occurrence of C. tennis was 7 to 10 weeks and 6 to 9 weeks for D. indices and P. bistrectins, respectively on three successive dates of sowing .The peak incidence of three insect pests were recorded in the fourth week of April and fourth week of May for C. tenuis and D. indics was third week of April and first week of May where as P. bistreatus was second and first week of April during 2003 and 2004, respectively .